FREQUENCY OF SOLITARY RECTAL ULCER SYNDROME AMONG PATIENTS PRESENTING WITH BLEEDING PER RECTUM AT A TERTIARY CARE HOSPITAL - SHERWANI, UK; AZMAT, S; EJAZ, M; IBRAHIM , M; SAFDAR, S; KOUSAR, R (Biological and Clinical Sciences Research Journal, 2023)
Solitary rectal ulcer syndrome is a multifaceted condition influenced by several clinical, histological, and endoscopic features. Treating this condition, especially in cases of relapse or non-responsiveness, requires a methodical and logical approach. This study aimed to determine the frequency of solitary rectal ulcer syndrome among patients presenting with rectal bleeding at a tertiary care hospital. This descriptive, cross-sectional study was conducted at the Department of Gastroenterology, Ibn-e-Sina Hospital/Multan Medical and Dental College, Multan, from 10-06-2022 to 10-06-2023. A total of 369 patients with rectal bleeding were registered in the study. Baseline investigations, including histopathology, were conducted to diagnose solitary rectal ulcer syndrome. Of the 369 registered patients, 237 (64.2%) were male, and 132 (35.8%) were female, with a mean age of 52.16 ± 9.05 years. Of these, 253 (68.6%) were from rural areas, and 116 (31.4%) were from urban areas. In 224 (60.7%), poor socioeconomic status was noted, while 145 (39.3%) had a middle-income level. Diabetes was present in 97 (26.3%), and hypertension in 134 (36.3%). The mean body mass index was 25.23 ± 1.57 kg/m2, and obesity was present in 56 (15.2%) patients. Solitary rectal ulcer syndrome was observed in 25 (6.8%) patients. The study concluded that there is a high frequency of Solitary rectal ulcer syndrome (SRUS) among patients presenting with rectal bleeding. Solitary rectal ulcer syndrome (SRUS) was significantly associated with increasing age, socioeconomic status, diabetes, hypertension, and obesity. All clinicians treating such patients should anticipate Solitary rectal ulcer syndrome (SRUS) for early diagnosis and proper management, which will improve their prognosis and quality of life.